Multi-Missioned Maritime Services: An Assessment of Proportional Approach of Inter-Agencies Operations in Nigeria and Malaysia (Journal of Governance and Development (JGD), 2020)
The interception of erring ships is one of the major tasks of maritime nations. The establishment of maritime agencies is done to protect seafarers, marine environments among others. Nigeria and Malaysia no doubt are two countries endowed with seas, and the two countries have enacted laws and established maritime agencies to tackle the menace of insecurity in ports and the maritime domains. The study compares the strategies for combating insecurity by maritime agencies in Nigeria and Malaysia. Interestingly, the two countries are also members of the International Maritime Organisation (IMO). Both countries, among other benefits, charge fees on cargoes loaded or unloaded in their ports. These charges significantly serve as sources of income, which enhances the economic development of the two nations. This paper examines the economic gains from the ports and maritime domain as well as the attendant risks inhibiting the fortunes derived from the seas despite legal and administrative machinery to surmount the challenges. The paper adopts methodological triangulation, and micro comparison to study or assess the phenomenon of various maritime security agencies at it enhances insight into their different approaches. This article gives a prognosis of some areas of benefits, interface, and shortcomings in the legal and administrative agencies of maritime security in Nigeria and Malaysia. It concludes by demonstrating that the laws regulating port and maritime security are virtually the same in both countries with little differences. It found that there is a lot to be learned from the implementation strategies of the Malaysian agencies especially in the areas operational disposition and this perhaps possible on the strength of basic amenities like stable electricity which is one of the panaceas to tame stowaway passengers among other insecurity in the port and maritime domain.